The Influence of Digital Marketing and Brand Awareness on Purchase Decision on Facetology Sunscreen Products in Shopee E-Commerce - Salman Alfarizi; Rizki Rizki; Soesanty Maulany (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the effect of brand awareness and digital marketing on purchasing decisions to buy Facetology sunscreen on E-commerce Shopee. A total of 385 respondents participated in this study, which used SEM SmartPLS. The results showed that purchasing decisions are positively and significantly influenced by digital marketing, positively and significantly influenced by brand awareness. This finding shows how important brand awareness and digital marketing are in influencing purchasing decisions to buy Facetology sunscreen on Shopee.